Innovation in Urban Tourism and its Determinants - Czernek , Katarzyna (Studia Oeconomica Posnaniensia, 2014)
Innovation is one of the key factors determining the competitiveness of cities. In tourism, however, it does not occur as often as in other sectors of the economy. This is mainly the result of specific features of tourism such as fragmentation in supply, seasonality and the predominance of small and medium-sized enterprises. The aim of this article is to present the specific determinants for the development and diffusion of innovation in urban tourism. The article consists of three parts, preceded by an introduction. The first part presents a definition and typology of innovation in the tourism sector as well as the types of innovation important for the development of tourism in cities. In the second part the most important approaches for analysing innovation stimuli are discussed (Schumpeter’s approach - stressing the role of entrepreneurship; Marshall’s approach - emphasising the role of location and network links; and the supply and demand approach). In the light of these approaches, the features of tourism and the ways in which they may hamper innovation in urban tourism are presented. The last part shows how, taking into account the presented determinants, a diffusion of innovation in cities can be possible. The directions for future empirical research in this area are presented as well.